Nature Ninja Edugame as an interactive learning solution for improving integrated science and social studies learning achievement in primary school - Paradisa, Fauza Cahya; Ratnaningrum, Ika (Universitas Islam Negeri Raden Intan Lampung, 2025)
Technology-based learning is increasingly evolving in elementary education, including developing interactive media to enhance student learning outcomes. This study aimed to develop and evaluate the feasibility, practicality, and effectiveness of the Nature Ninja Edugame based on Articulate Storyline for the fifth-grade Natural and Social Sciences. The research followed a Research and Development approach with the ADDIE model. Data collection techniques included observations, interviews, questionnaires, documentation, and tests. Validation results indicated high feasibility, with an average score of 90% from media and material experts. The t-test effectiveness test showed that Sig. was lower than 0.05, indicating a significant difference between pretest and posttest learning outcomes. Additionally, the N-gain test showed a moderate increase (0.6336) in the small-scale trial and a high increase (0.7114) in the large-scale trial. Based on the questionnaire results, teacher and student responses were highly positive. The study concludes that Nature Ninja Edugame is effective, feasible, and practical for enhancing fifth-grade students’ science and social studies learning outcomes. This research highlights the importance of innovative and interactive learning media as an effective strategy to improve student performance and enrich technology-based learning experiences in elementary education.